“She liked the picture so i think she liked it”. Unpacking the social practice of liking - Beata Jungselius (Netcom)
In this paper, the social practice of liking on Instagram is unpacked. Based on in-depth interviews with 16 Instagram users, the findings suggest that the meaning making process of interpreting Likes is complex. The findings show that in order to understand Likes, users create social reference points to interpret Likes they do and do not receive. Drawing upon these findings, ways of understanding the complexity of this seemingly simple actions as expressions of social support are discussed.